Pink Ribbon Day as the International Breast Cancer Awareness Campaign - Abhirama Swastyayana Dian Perdana (President University, 2018)
Currently, with the booming of New Media, it is not uncommon to see causes and campaigns meant to raise awareness on certain issues. One of the all-time viral campaigns was ‘ALS Ice Bucket Challenge’ campaign videos performed by well-known celebrities. In relation to causes and campaigns, on the 1st of October, our attention is drawn towards the Pink Ribbon Day – known as the International Breast Cancer Awareness Day. Not only that, there is currently an attention-getting Cancer Awareness campaign in many social media – Stand Up to Cancer (SU2C) Campaign – which has drawn the attention of those whose lives have been touched by the various devastating Cancer illnesses. This paper discusses and analyzes the SU2C campaigns in relation to its reliance on celebrity endorsement in achieving its purposes. The case of SU2C is analyzed within the framework of Circuit of Culturetoanalyze how the public relations theory and Celebrity Humanitarianism may inform the various practices of public relations in the world. Not only that, through the reflections in the Circuit of Culture, the paper also elaborates the possibilities of how the analysis of the SU2C campaign can be used to influence other cancer awareness campaigns, particularly in Indonesia.Keywords: New Media, Campaign, Circuit of Culture, Celebrity Humanitarianism